2016
DOI: 10.1021/acsami.6b08823
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Cellular Knockdown Mediated by siRNA Nanovectors of Gemini Cationic Lipids Having Delocalizable Headgroups and Oligo-Oxyethylene Spacers

Abstract: The use of small interfering RNAs (siRNAs) to silence specific genes is one of the most promising approaches in gene therapy, but it requires efficient nanovectors for successful cellular delivery. Recently, we reported liposomal gene carriers derived from a gemini cationic lipid (GCL) of the 1,2-bis(hexadecyl dimethyl imidazolium) oligo-oxyethylene series ((C16Im)2(C2H4O)nC2H4 with n = 1, 2, or 3) and 1,2-dioleyol phosphatidylethanolamine as highly efficient cytofectins for pDNA. On the basis of the satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 70 publications
1
34
1
Order By: Relevance
“…In the present work, the GCL C 3 (C 16 His) 2 was used in combination with the helper lipid MOG as a nanoplatform to introduce gene material into HeLa and T731 cancer cells in an efficient and safe manner. A molar fraction (α) with respect to the GCL of 0.2, which implies a larger content of the neutral helper lipid (MOG) in the mixture, was chosen since it was revealed as optimal in previous works with similar siRNA nanocarriers [ 38 , 43 ]. The efficiency of the siRNA nanovector relies on a siRNA packing-unpacking mechanism conducted by the lipid mixture, which is responsible for the compaction of siRNA and its subsequent delivery inside the cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present work, the GCL C 3 (C 16 His) 2 was used in combination with the helper lipid MOG as a nanoplatform to introduce gene material into HeLa and T731 cancer cells in an efficient and safe manner. A molar fraction (α) with respect to the GCL of 0.2, which implies a larger content of the neutral helper lipid (MOG) in the mixture, was chosen since it was revealed as optimal in previous works with similar siRNA nanocarriers [ 38 , 43 ]. The efficiency of the siRNA nanovector relies on a siRNA packing-unpacking mechanism conducted by the lipid mixture, which is responsible for the compaction of siRNA and its subsequent delivery inside the cells.…”
Section: Resultsmentioning
confidence: 99%
“…This effect has also been observed in lipoplexes formed by the lipid mixture C 3 (C 16 His) 2 /DOPE and pDNA [ 26 ] and in others lipoplexes that contain GCL lipids bearing the imidazolium ring in their structure [ 56 , 66 ]. By contrast, the effective charge of siRNA is considered to be the same as its nominal one ( ), as reported in the literature for either linear DNA (with thousands of base pairs, as calf thymus or salmon sperm DNA) [ 56 , 57 , 58 ] or short RNAs (with 19–25 bp) [ 38 , 67 ]. Considering these results, it can be concluded that the formation of lipoplexes is mainly driven by electrostatic forces between the oppositely charged cationic lipid and the anionic siRNA molecules.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous artificial systems formed by lipids [7][8][9], polymers [10][11][12], dendrimers [13,14], carbohydrates [15,16], cyclodextrins [17,18], polypeptides [19,20], and nanoparticles [21,22] (among others) have been studied to avoid the adverse effects produced by viral vectors in biological media, such as immunogenicity and inflammatory responses [23,24]. In particular, cationic lipids have been investigated in detail as useful tools [25,26] because they present low toxicity and are easily synthesized, as well as establish strong electrostatic interactions with DNA/RNA double strains through their positive charges affording lipoplexes. Furthermore, the nanometer size and net positive charge of these complexes favors their internalization across the cell membrane, allowing the delivery of the cargo in the cellular cytoplasm and resulting in moderate-to-high transfection efficacy.…”
Section: Introductionmentioning
confidence: 99%